Induced redox responsiveness and electroactivity for altering the properties of micelles without external stimuli - Glavas, Lidija (Royal Society of Chemistry, 2014)

(untitled)
Control over micelle properties is vital in the field of drug delivery, and the ability to modify these properties in order to trigger dissociation is highly desirable. We prepared polymeric micelles with the ability to undergo dissociation over time without the need for external stimulation by incorporating an electroactive and redox responsive segment into amphiphilic copolymers. The incorporation of this segment also provides the ability to tailor the critical micelle concentration (CMC) and micelle size of the copolymers. Amphiphilic PEG–PLA copolymers were functionalized by coupling to an aniline pentamer in two different oxidation states (leucoemeraldine and emeraldine state). The incorporation of the electroactive and redox responsive aniline pentamer decreased the CMCs and the micelle size, independent of the oxidation state. However, the copolymers with the aniline pentamer in the leucoemeraldine state had significantly lower CMCs than the copolymers with the aniline pentamer in the emeraldine state. Simultaneously, stability tests performed on the functionalized micelles demonstrated the oxidation of the aniline segment, from the leucoemeraldine to the emeraldine state, over time. The oxidation led to an increase in the CMC, and the copolymers could thereby represent an excellent starting point for triggering drug release without external stimuli.